2021
DOI: 10.1073/pnas.2101161118
|View full text |Cite
|
Sign up to set email alerts
|

Translational shutdown and evasion of the innate immune response by SARS-CoV-2 NSP14 protein

Abstract: The ongoing COVID-19 pandemic has caused an unprecedented global health crisis. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of COVID-19. Subversion of host protein synthesis is a common strategy that pathogenic viruses use to replicate and propagate in their host. In this study, we show that SARS-CoV-2 is able to shut down host protein synthesis and that SARS-CoV-2 nonstructural protein NSP14 exerts this activity. We show that the translation inhibition activity of NSP14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
177
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(183 citation statements)
references
References 46 publications
5
177
1
Order By: Relevance
“…In our analysis of the promoters of early upregulated genes, we also detected enrichment for binding sites of transcription factors involved in the interferon response. In support of our findings, recent reports showed that Nsp14 reduces the expression of INFb and ISG luciferase reporters (Yuen et al, 2020), as well as the expression of proteins involved in the NFkB pathway (Hsu et al, 2021;Li et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In our analysis of the promoters of early upregulated genes, we also detected enrichment for binding sites of transcription factors involved in the interferon response. In support of our findings, recent reports showed that Nsp14 reduces the expression of INFb and ISG luciferase reporters (Yuen et al, 2020), as well as the expression of proteins involved in the NFkB pathway (Hsu et al, 2021;Li et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…However, although IMPDH2 protein is conserved (Hedstrom, 2009), the transcription factor activity of IMPDH2 has not been demonstrated in mammalian cells. Furthermore, IMPDH2 can associate with polyribosomes in mammalian cells and modulates the translation of specific mRNAs (Hsu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations